Who's afraid of China? the challenge of Chinese soft power - Barr, Michael (London, 2011)
If China suddenly democratised, would it cease being labelled as a threat? This provocative book argues that fears of China often say as much about those who hold them as they do about the rising power itself. It focuses not on the usual trope of economic and military might, but on China's growing cultural influence and the connections between China's domestic politics and its attempts to brand itself internationally. Using examples from film, education, media, politics, and art, Who's Afraid of China? is both an introduction to Chinese soft power and a critical analysis of international reaction to it. It examines how the West's own past, hopes, and fears shape the way it thinks about and engages with China and argues that the rising power touches a nerve in the Western psyche, presenting a fundamental challenge to ideas about modernity, history, and international relations.
Keywords: China-Growung cultural influence